Principles and Mechanisms of Wildlife Population Persistence in the Face of Disease - Russell, Robin E.; DiRenzo, Graziella V.; Szymanski, Jennifer A.; Alger, Katrina E.; Grant, Evan H. C. (Frontiers in Ecology and Evolution, 2020)
Emerging infectious diseases can result in species declines and hamper recovery efforts for at-risk populations. Generalizing recommendations for reducing the risk of pathogen introduction and mitigating the effects of disease remains challenging and inhibits our ability to provide guidance for species recovery planning. Given the growing rates of emerging pathogens globally, we identify key principles and mechanisms for maintaining sustainable populations in the face of emerging diseases (including minimizing the risk of pathogen introductions and their future impacts on hosts). Our synthesis serves as a reference for minimizing the risk of future disease outbreaks, mitigating the deleterious effects of future disease outbreaks on species extinction risk, and a review of the theoretical and/or empirical examples supporting these recommendations.